2006
DOI: 10.3310/hta10130
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial, observational study and assessment of cost-effectiveness of the treatment of varicose veins (REACTIV trial)

Abstract: Standard surgical treatment of varicose veins by saphenofemoral ligation, stripping and multiple phlebectomies is a clinically effective and cost-effective treatment for varicose veins, with an ICER well below the threshold normally considered appropriate for the funding of treatments within the NHS. Injection sclerotherapy also appears to be cost-effective, but produces less overall benefit, with a higher ICER than surgery for patients with superficial venous reflux. In minor varicose veins without reflux, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 129 publications
3
133
0
3
Order By: Relevance
“…The M:F ratio found in our study is in sharp contrast to the ratio mentioned in most of the western literature, where more females were suffering from this disease. 8,11,12,18,21,26 However in the study conducted by Jain et al, 41 of the 42 patients were males; by Masuda et al 42 of the 68 patients were males. 12,13 Majority of our patients were young with a mean age of 35.32 years in both group.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The M:F ratio found in our study is in sharp contrast to the ratio mentioned in most of the western literature, where more females were suffering from this disease. 8,11,12,18,21,26 However in the study conducted by Jain et al, 41 of the 42 patients were males; by Masuda et al 42 of the 68 patients were males. 12,13 Majority of our patients were young with a mean age of 35.32 years in both group.…”
Section: Discussionmentioning
confidence: 78%
“…11 Also comparing the local wound related complication in surgery group with work of Michaels JA et al who found wound related complication in only 2.4% of patients our study group had more of local wound related complications. 18 In our study complications in the foam sclerotherapy group were tolerable and transient like discomfort in walking, tenderness etc. and did not require any active intervention, which are again comparable to the published studies.…”
Section: Procedures Timementioning
confidence: 93%
See 2 more Smart Citations
“…Hip [14] and knee [15] replacements, and hernia [16] and varicose vein [17] repair cost less than £10k per QALY gained. Elective procedures such as these are often first to be reduced when the NHS is short of resources.…”
mentioning
confidence: 99%